2008
DOI: 10.1007/s11605-008-0599-3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy-Assisted Distal Gastrectomy for Gastric Cancer

Abstract: The authors conclude that laparoscopy-assisted distal gastrectomy is a safe and useful operation for early-stage gastric cancers. If patients are selected properly, laparoscopy-assisted distal gastrectomy can be a curative and minimally invasive treatment for gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…After reading the full texts of the remaining papers, 24 studies were removed as they only reported the outcomes of LG for AGC whereas no controlled or matched cases treated by OG were available. Among the remaining articles, 19 studies [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] were excluded because EGC cases were mixed with AGCs in the cohort studies and data on AGCs were not extractable. Eight studies were further deleted for the following reasons: 2 studies were ongoing randomized controlled trials (RCTs) that only described study design and patient enrollment criteria without results reported [56,57]; 2 studies had overlapped enrollments with former research [58,59]; 1 study reported incomplete data that were not suitable for analysis [60]; and 3 studies discussed other issues irrelevant to the topic of this meta-analysis [61][62][63].…”
Section: Resultsmentioning
confidence: 99%
“…After reading the full texts of the remaining papers, 24 studies were removed as they only reported the outcomes of LG for AGC whereas no controlled or matched cases treated by OG were available. Among the remaining articles, 19 studies [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] were excluded because EGC cases were mixed with AGCs in the cohort studies and data on AGCs were not extractable. Eight studies were further deleted for the following reasons: 2 studies were ongoing randomized controlled trials (RCTs) that only described study design and patient enrollment criteria without results reported [56,57]; 2 studies had overlapped enrollments with former research [58,59]; 1 study reported incomplete data that were not suitable for analysis [60]; and 3 studies discussed other issues irrelevant to the topic of this meta-analysis [61][62][63].…”
Section: Resultsmentioning
confidence: 99%
“…In most studies, the authors concluded that LADG was comparable to or sometimes better than ODG in terms of postoperative clinical outcomes [3,9,12,13,14,15,16,17]. Although recent studies revealed that age, sex, and BMI were important factors that influence the outcome of surgery, few studies that controlled these factors have been published.…”
Section: Discussionmentioning
confidence: 99%
“…For mucosal EGC, a D1 dissection with removal of 1 and 3-6 stations according to JGCA is adequate [1,33], the same as in a modified D2 dissection for mucosal or submucosal EGC [36]. For EGC of the lower third, distal gastrectomy is generally performed [15,17,19,21,22,24,25,29,36], but SG with a 6-cm safety margin has been described also [10,13,26], mainly for the possible presence of multifocal cancer [37]. As a result of our policy, all of the patients cured of EGC have the resection margins free of disease and all but one with Pen A tumor are alive and disease-free in the follow-up.…”
Section: Respect Of Oncologic Principlesmentioning
confidence: 99%
“…Adversely, invasiveness through the gastric wall is sometimes underestimated during the preoperative workup; thus, the role of D2 nodal clearance in EGC has been emphasized [3,[8][9][10]. That laparoscopy can be feasible and effective in the treatment of gastric cancer is apparent from the results in many articles [8,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], some of which compare also AGC data on survival [10,12,13,15,19,24]. Robotics can improve a surgeon's dexterity and may be especially helpful during maneuvers in restricted fields such as in extended lymphadenectomy [16,[26][27][28][29].…”
mentioning
confidence: 99%